Türk Pop Müziğinde Türk Müziği Etkilerinin Analizi - Erişçi, Çelik (Sosyal Bilimler Enstitüsü, 1996)
Türk pop müziği 1980'li yıllardan itibaren gündemdeki arabesk müziğin yerini almaya başlamıştır. Bu hızlı gelişme 1990'lı yıllarda en hızlı noktasına ulaşmış, neredeyse pop müzik kasetleri dışında hiçbir kaset satmaz olmuştur. Her olayın bir sebebi olduğu gibi Türkiye'de müziğin bu hızlı ve değişim gösteren gelişmesinin de bir sebebi vardır. Türkiye'de müzik, müzik dinleyicisi olduğu için vardır. Yeni nesil, telekominikasyon imkânlarından, sosyal, siyasal ve ekonomik olaylardan etkilenmektedir. Bu etkilenmelerin sonucu, en kolay duygu iletişim kurma aracı olan müzikte kendini göstermektedir. Osmanlı imparatorluğu' nun yıkılmasını takiben, Cumhuriyet rejimi sırasında Türkiye'de önemli müzikal değişimler olmuştur, önceleri Türk mûsikîsi varken, daha sonraları yavaş da olsa batı müziği etkilenmeleri, taklitleri ve eğitimi başlamıştır. Sonradan bu değişim sürmüş, yabancı batı müziği kaynaklı parçalara Türkçe sözler yazılmış ve Türk Hafif Müziği oluşmuştur. Türk Hafif Müziği, Türk Halk ve Türk Sanat Müziği enstrümanları karışımının kullanımından ve kurala bağlı olmayan bir ses sisteminde ortaya çıkan müziğe Arabesk denilmiştir. Son olarak bu müzik de yerini Pop Müzik patlamasına bırakmıştır. Türkiye'deki bu hızlı müzikal değişimin belli başlı sebepleri vardır. Bunlar siyasal, sosyal, ekonomik, kültürel sebepler olarak sıralanabilir. Eknomik problemleri yaşayan halkın bu sıkıntıları müzikte de kendini hüzün, sıkıntı, isyan, çaresizlik ve sonuçta da arabesk bir anlayış olarak göstermiştir, önce taklit daha sonra tatbik olarak kendini gösteren Pop Müziği, yabancı kaynaklı müziklere Türkçe söz yazılarak başladı. Ardından kendi bestelerimiz ve ve sözlerimiz kullanılmaya başladı. Böylece bir anlamda yabancı müzik ve söz bağımlılığından kurtulunarak müzikal kültür anlamında bağımsızlık elde edildi. Fiziksel ve biyolojik anlamda daha hızlı düşünmeye başlayan Türk insanının dinlediği müzikte de bir hız, bir hareket, bir dinamizm görülmeye başladı. Bütün bunlar gözönünde tutulduğunda Türkiye'deki müzikal değişimin özellikle Pop Müziğini öne çıkaran değişimin birtakım etkenlere bağlı sebepleri olduğu ortaya çıkar. Burada önemli olan ise bir tarih birikimi olan Türk Müziği'nin çok dinlenir bir durumda olan Pop Müziği'nin içinde ne kadar yer aldığıdır. Örneğin; aynı olmasa da ritm veya makam formlarının Pop Müziği içindeki etkileri görülebilir. Türk Müziği, Türk Halk Müziği enstrümanı kullanımının oyun havası formunu andıran enstrümantal emprüvize çalışmalar ya da uzun hava veya gazel türü serbest şan çalışmalarının Pop Müziği sauşlanndaki etkisi yadsınamaz. Bu tür müziği tanıyan halkın daha modernize olmuş bir müziği tanımaması düşünülemez. Burada düşünülmesi gereken yeni bir müzik türünün olup olmadığı, köklü bir değişimin yaşanıp yaşanmadığıdır. Görülen o ki, yenilik denirken bir ses sistemi deforme edilmektedir.

When we analyze the type of music being conducted today versus the past, we can conclude that the bridge on which it has been built on has gone through a radical change. Beginning in the Middle Ages and spanning the Turkish revolutions, history has shown us that the first musical sounds were in the form of rhythmic intonations. It is also a proven fact that the "kopuz" (as it was called in medieval times) or the "ud" (lute) as it is called now, was a musical instrument first used by the Turks. The Turks settled in Anatolia in the 1 1 th century, Turkish music compositions written from the 13 th century on exiist. Turkish music entered into its golden era during the 16th century. The classical song writing style started during this period. Additionally, the note system used in Turkish music today was created during this century. Additional successes in the music field were felt wqith the rise of the Ottoman Empire. The sultans kwere content economically and politically so they were able to show interest in the arte. Furthermore, good songwriters existed among the sultans. The sultans protected individuals who were interested in music and in later years opened a music school. The most important distinction during this era is that the sultans and other artists involved in Turkish music were properly trained and educated. This fact demonstrates the importance of education in the development of music in a society. The "radiant" period created by the Ottomans allowed the society to have a devotion and passion for the arts-especially music. This devotion along with the emphasis placed on proper education played a major role in the creation of classical compositions. The end of the Turkish kWar of Independence and the creation of the Turkish Republic affecting all walks of life in Turkey, set the stage for additional changes to misc concepts. During this time, interest in Turkish Classical music continued. However, at the same time,e Classical Western Music was bom. The type of music that matured and developed during this period affects how music is conducted today. Initially, music and cassette recordings were carried out using acoustic instruments. This was later replaced with metallic instruments as technology increased. The music industry was also affected by the improvements in technology. The name "keyboard" given to electric pianos increased the speed by which music is made. The keyboard has the ability to generate digital sounds of various different instruments, so time is now saved during studio recordings. -vn- In the musical sense, the most accurate sounds are now attained. However, the problem we now face is mat music mat is not natural khas no soul. AH of the above discussions mention previous eras, however, we can consider the time we live in now as its own era as well. In a sense, we can say mat teh growth of science and introspection has increased mankind's knowledge and appreciation of music. In fact, when we look at the metronome speed of old Turkish music compositions, it is slow compared to today's music. An artist is a person who possesses a god-gived gift and has the education, know-how and talent which puts him on a different plane than others. Also, the artist takes these emotions and gained knowledge and showcases the results. A musician ewpresses himself by sharing his thoughts and feelings in a musical environment. The past and the present shows us mat a musician who knows the intonation systems well, has obtained the education and who can play an instrument can produce very good music. It is interesting to note that in our day, and especially in the fast growing pop music industry, the qualities we listed above do not ewist in most artists. This leads to a less creative and productive artists group which affects the ewpectations of a deprived society. This society is looking for artists who understand their need and to knourish and fill the gap that exists. As a result, rapid changes are occurring in the industry. Research findings indicate that most of today's artist not only does not have a conservatory bacground, but a university education does not exist either. Since most do not play kor have an understanding of musical instruments, they lack the ability to compose music. The easies way to understand Turkish or Western music is to play a musical instrument. Artists who do not have this ability ruin their vocal cords, cannot be creative and go no further than beings imitators. Music is one of the most important fgield's in the Arts arena. The economic, political and cultural climates as well as the media influences the society's tastes and desires. For example, during the Nev Year's season purchasing increases. An individual who normally does not buy cassettes will do so just to do something different. 1 This type of consumer behavior will change the graphic of cassette sales in a apositive way and sales will increase. The interesting point here is that impulse buying is occurring. Consequently, the consumer is purchasing a cassette that hits the market during this season not for musical type, but due to availability. So, it has bee noted that the next time a consumer makes a purchase, it will be of the same type of music. It is quite interesting to note all the elements that are thought of by a consumer before a cassette of an artist is purchased. Such things as the color of the cassette cover; the artist's age, education level, past musichistory, and instruments played are considered. Additionally, the release date of the cassette (day/month/year), whether the artist is a man or a woman and what he or she wears on stage are also important to consumers. -vra- When we observe the situation as stated above, we can say that in a society that carries traditional Turkish music in its memory will find correlations and purchase pop music tapes as they recognize and notice similar characteristics such as language, rhythm and sound. The reality of the matter is that today's music is nothing more than an alteration or dressing up of the past and presenting it as a new and fresh remembrance. So, a boom or revolution has not accurred in the music industry. The most important conclusion here is not the feet that pop music has been influenced by Turkish music, but the fact that the instruments used has ruined the sound systems created by traditional Turkish music. This thesis will review and evaluate the reasons behind the above hypothesis and to point out the influence this has on music today. In the process of doing this,important questions and concerns are being raised. Information regarding the lack of music quality of cassette recordings from the past is not being considered. To date, there are no archives ofmusical compositions and many older cassettes kcannot be found or do not exist. Since this is the case and the ability to listen to these tapes is not possible, no additional information on this subject can be obtained. In an effort to research the infuences that Turkish music has on Turkish pop music, I examined and scrutinized twenty-five best-selling pop music artist recordings. The goal of my research was to find the points mey hava inconmon. I divided my thesis into six categories. They are : The general structure of the recording, cassette cover, chronological order of the cassette, musical composition and songwriting style, and finally information about the artist. Additionally, I did not just analyze the rhythm and sound of the music. As I previously mentioned, I researched how the economic and political environment affects the buying habits of consumers and how much of a role this actually plays. In fact, in our day, I've noticed that for the sake of art such elements as image, newness, promotion and recognition erode the musical valve and placve emphasis on these non musical variables. An example of this hypothesis can be exaplained as follows. The first part of my research and study is comprised of information about the cassette recordings. The first section looks at cassette title selection. Only two (2) out of the twenty-fire (25)cassette used in my study had the artists' name as it's title. The other twenty- three (23)artists' titles were well known songs from the cassettes. From this, I come to the following conclusion. Roughly 82 % of cassettes mat use a popular song as a title, caused sales of the cassette to increase. On the other hand, I noticed that when the title of the cassette was the artist's name, the musical valve abandoned and the artist became the focus. In this sitvation, sales fell to such levels as 8 %. We can arrive at another conclusion from this sitvation. That is, when commercial valves superesede musical valves, artists and songs that are of worth and permanence are not sustained. I took my research one step furthere. I looked at whether the title of the cassette was the most popular song on the cassette or a random selection. Eight (8) out ot the twenty-five (25) cassette recordings researched used a well-known popular song as it's title where as seventeen (17) of them had titles -DC- of less-popular songs. As a result, 68 % of the public looked at the musical quality of the cassette when making a purchasing decision instead of how popular a particular song was. This thesis is the first of its kind and is not supported by any previaus research studies. Additionally, my thessis is not based on mathematical variables, so I have attempted to stay away from this. Hawever, up to a certain point, I had to use some figures in my findings. Very simple mathematical calculations were used to determine, certain hypotheses. For example, if two (2) out of teventy-five (25) artists used their name as a cassette title, this translates to 8 %, therefore 92 % of artiste used a song from the cassette as its title. In fact, through the entire thesis, I used the same percentages and compared theme to the mutual points shared. Some intereseting findings came aut of this. For example, vithout fail, the "minor" music style is the preference of the Turkish public. They do not preter slow "metronome" songs. Another ewample is the sales of cassettes increase when the orifinal instruments are used in recording the song versus using computer generated sounds where the natural quality of the sound is lost. Songs under three minutes nor over four minutes were listened to. Musical instruments that are appropriate tho the type of music being played were preterred. In general, the public preters it when the artist is the sole vocalist versus having back-up singers. From this conclusion we notice the influences of Turkish Music which is based on the singular sound instead of the several vocal sounds of the "Tampare" style, is evident in todays pop music. Also pop music is influenced by other Turkish music such as "taksim", "gazel", instrumental and emphasis on words musical styles which have been modernized. In reference to the we of words, we see that a large portion of songs are written in short prose using simple words. Especially, the continuas repetition of the chorus section until it is ingrained in our minds has on impact on cassette sales which is in the 48 % range. A very small portion (4 %) of songs written use slang. As a result, we notice the importance the public places on the "meaning" of the song. From time to time, we still see the dependence on foreign languages (about 32 %). Especially, the use of Arabic and Persian mixed with Turkish shown the effects of the Ottoman era. In general, the public preters male artists whe are tenors. Also on the music scene, in the minority, are women artists who are altos. This shows hov the exolution of the society affects preferences. In all this, it is very important to point out that unfortunately most artists (men and women) are less educated and their conservatory education is very low. As a result, the number of artists who play musical instruments are decreasing. I feel that this is the most important fact. An artist who cannot read notes, play a musical instrument, who has not taken any singing lessons and in fact probably has no literature back graund leads to the conclusion that proper Turkish language skills are -X- lacking. We can go so far as to say that this artist is someone who mumbles tunes, puts this on his cassette, writes and composes songs with abilities that are lacking the above skills. To camouflage the shortcomings of the artist, the knowledgeable musicions and arrangers who implement the final product are the people that should also be acknowledged. Since lie situation is like this in Turkey, what develops in the name of music is nothing more than a vicious circle. The next element mat is betore us is the state of the cassette cover when it reaches the consumer. Here we arrive at two conclusions. First, 68 % of the consumers want to see a picture of the artist depicting head and shoulders only. Secondly, 80 % of the consumers preter this picture to be in color. We can reach the conclusion that consumers do not preter black and white pictures and graphics on cassette covers. So, the artist who spends time and energy developing computer induced graphics or black and white drawings is not appreciated. Also, on 76 % of cassette covers, the artist is in casual sports wear. In actuality, it is not the outfit warn by the artist that is ot importance rether it is the music quality mat comes to the for efiront. Another important point is that most performers use their own compositions and lyrics.. When developing caissette recordings. This shows us that the artist is the person who can best explain his tthoughts and feelings in a song and the public is awore of this. Another important selling point of cassettes is the pronounced rhythmic qualities of the music. For example, the singular sound thata defines Turkish kmusic does not cantain any unbalonced rhythms. But, the use of the "sofyan" or "düyek" rhythms are still mainly used with minor changes. Consequently, a rhythmic style called "velvele" that is the use of "eights" or "main sets" notes that are played create a new rhythmic style mat contains the main principles of the "velvele" style. This is the new rhythmic style that is at the point of explosion in pop music today and used the most often. In conclusion, all ot the above factors are examples in defining the development of Turkish pop music. The most needs to be considered is that musical culture and guality should not become decadent.
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 1996
Thesis (M.A.) -- İstanbul Technical University, Institute of Social Sciences, 1996
Keywords: Müzik; Popüler müzik; Türk müziği; Türk pop müziği; Music; Popular music; Turkish music; Turkish pop music